Filantropia e inclusão educacional no ensino superior: estudo de caso do Centro Universitário Franciscano-Santa Maria-RS - Anjos, Cáli Rosi Souza dos (Universidade do Vale do Rio do Sinos, 2007)
This dissertation has as objective the study of the philanthropy and its mediation with the State and the Civil Society, concerning the educational inclusion in college teaching. In the current conjuncture, the philanthropy depends on an legislation, which, breaking the benevolent and helpful character, gives to the theme the notion of rights to the ones in need of it, and deviate it from the idea of the “merit”. To accomplish the study, it was used a Study Case approach (with philanthropic students) in which was applied a questionnaire interview with students and managers from the Franciscan University Center. The intention was to visualize the comprehension and the understanding they have about this form of educational inclusion, also discussing the importance of better socio-economical condition of life to the students that attend this kind of educational inclusion. The results show that the entrance and the permanence in college teaching of many students, which can not enter in public universities, only o
Philanthropy and educational inclusion in college teaching. Study case of the Franciscan University Center-Santa Maria- RS
Keywords: ensino superior; inclusão educacional; filantropia; educational inclusion; philanthropy; Ciências Sociais Aplicadas